Communal and Individual Learning Contexts as They Relate to Mathematics Achievement Under Simulated Classroom Conditions. (September 2017) - Coleman, Sean T.; Bruce, Adrian Wayne; White, Lamar Jamison; Boykin, A. Wade; Tyler, Kenneth
The current study builds on previous communalism research by exploring the enduring facilitative effects of communal learning contexts on academic achievement for African American children over extended time and while calling on critical thinking skills. In addition, this study sought to explore the communalism construct in a more applied academic environment that approximated real classroom conditions. This study examined performance differences in fraction problem solving among 96 low-income African American students in Grades 3 to 6 participating in either a communal or individual learning context. Pretest to posttest gains showed that students randomly selected for the communal learning context significantly outperformed students who learned in the individualistic context. Additionally, communal learning students outperformed their individual counterparts during each weekly domain assessments. Several promising results obtained draws the communalism construct to a more applied culturally relevant pedagogical tool.